Shaping change locally: a place-based STEM project’s influence on rural elementary and middle grade students - Mercier, Alison K.; Sivitskis, Alexander J.; Torbert, Jeffrey; Vallier, Kelly (Frontiers in Education, 2025)
IntroductionPlace-based education (PBE) seeks to integrate local environmental, cultural, and community contexts into learning. With instruction grounded in students’ lived experience, this approach has the potential to enhance engagement and foster identity development, particularly in STEM disciplines. However, research on how PBE may influence STEM identity and agency development, especially in rural contexts, remains limited.MethodsThis study examines the effects of a place-based STEM project on fourth, fifth, and sixth-grade students in a rural school, focusing on identity affiliations, self-perception, and community engagement. Using a case study approach with elements of participatory action research, we analyzed pre- and post-project surveys, focus group interviews, and qualitative reflections.ResultsFindings indicate that students experienced significant shifts in their identity affiliations, particularly as advocates, problem-solvers, and community members. Students developed a stronger sense of environmental responsibility and STEM competence, engaging in authentic scientific inquiry and public advocacy. The project fostered interdisciplinary learning, real-world problem-solving, and strengthened students’ sense of agency through their involvement in a local wildlife-vehicle collision mitigation effort.DiscussionThis study highlights the role of PBE in supporting STEM identity formation and civic engagement, demonstrating how locally relevant projects can empower students to see themselves as capable STEM learners and active community participants. The findings contribute to the growing body of research on place-based STEM education, emphasizing its potential for enhancing student engagement, agency, and identity development in rural contexts.